Knowledge, attitude and practices (KAP) of intestinal helminths and protozoa infections among parents of Sekolah Kebangsaan Bukit Goh and Sekolah Kebangsaan Sungai Talam, Kuantan, Pahang, Malaysia - Mat Yusof, Afzan; Mohammad, Mardhiah; Roslan, Nur Zulaikha; Hisamudin, Nur Hazirah (2014)
Intestinal helminths and intestinal protozoa infections are one of the leading causes of diseases among young people and adults in the world today. Low socio- economic status, overcrowded areas, poor environmental sanitation, inappropriate garbage disposal, lack access to safe water and unhygienic personal habits are among the factors which contribute to the increase number of prevalence in intestinal parasitic infection. The study is crucial and beneficial to provide the latest data and information for actions by government and for appropriate control measures to be determined and undertaken. Hence, this research aimed to evaluate and compare the KAP of intestinal protozoa and helminthes among parents of Sekolah Kebangsaan Bukit Goh and Sekolah Kebangsaan Sungai Talam in Kuantan, Pahang. A cross-sectional study was conducted and a total of 136 parents of school children were selected randomly from both urban and peripheral areas. Sixty eight respondents from Sekolah Kebangsaan Sungai Talam represent the parents of school children in urban area and sixty eight respondents from Sekolah Kebangsaan Bukit Goh represent the parents of school children in peripheral area. In this study, fifty percent of the respondents from Bukit Goh did not know that faeces are the primary source of infection and they have never heard about intestinal parasitic infections. However, the findings showed that there was no significant difference between KAP of intestinal helminths and protozoa infection among parents from both areas in terms of low income and high income. In this study, the income factor did not give any guarantee on the knowledge, attitudes and practices toward the intestinal helminths and intestinal protozoa infections. Awareness to the public regarding the intestinal parasites and good hygiene behavior were needed to expose the public about the intestinal helminths and protozoa infections.